Síntese quimioenzimática da (S)-5-hidroxi-2-(1- hidroxietil)-nafto[2,3-b]furano-4,9-diona e emprego das leveduras Candida tropicalis e Pichia membranifaciens na redução da acetofenona e derivados - Araújo, Daniel Marcos de Freitas (2010)
Herein we report the employment of lipases and alcohol dehydrogenases for production of chiral molecules through kinetic resolution of secondary alcohols and reduction of ketones, respectively. In the first part of this work it was prepared a naphtoquinone with citotoxic activity employing a chemoenzymatic route based on seven reactional steps. From 1,5-dihydroxynaphtalene we prepared 5-hydroxy-2-(1-hydroxyethyl)naphtho[2,3- bifuran-4,9-dione, a secondary alcohol that, was submitted to kinetic resolution employing two commercial lipases, lipase from Candida antarctica B (CAL-B) and lipase from Pseudonionas cepacia (PSC). After 50% of conversion, the alcohol was recovered with 42% yield and ee >99% (S) by the use of CAL-B in two hours of reaction. Similarly, using PSC the alcohol was recovered with 45% yield and >99% (S) of enantiomeric excess. Both cases, leaded to the corresponding acetate with 43-44% yield and enantiomeric purity >99% (R). Alternatively, the alcohol was obtained by the use of an enantioselective bioreduction method promoted by alcohol dehydrogenases. Six commercial enzymes were selected for this step - A (Rhodococus ruber), CP (Candida parapsilosis), LB (Lactobacillus brevis), PR2, RS1 (Rhodococus sp.) and T o (Thermoanaerobacter sp.). A detailed investigation and optimization of the parameters leaded us to use ADH A to obtain alcohol (S) with 92% yield and ee >99%. In the second part of this work a screening was realized to select enzymatic microbial sources for reduction of carbonyl compounds. Initially, eight yeasts were chosen (two strains of Candida krusei, Candida guilliermondi, Candida rugosa, Candida tropicalis, Kluyverornyces lactis-similar, Pichia anomala and Pichia mernbramfaciens) which were submitted to a colorimetric assay for identification of alcohol dehydrogenases (ADHs). This revealed us that all strains are ADH producing sources. After that, these ones were employed as bioreducing agents of a standard substrate, acetophenone. The best results were obtained by using Candida tropicalis and Pichia membranifaciens as biocatalysts with conversions of 62 and 75% and enantiomeric excesses of 98% and 99% (S), respectively. Further, C. tropicalis and P. membranifaciens performed the reduction of some acetophenone derivatives. The best results were found to be for the nitrocompounds with complete conversions and ee between 96-99%.